Fig. 3 in Molecular identification of two Eimeria species, E. uekii and E. raichoi as type B, in wild Japanese rock ptarmigans, Lagopus muta japonica - Matsubayashi, Makoto; Tsuchida, Sayaka; Kobayashi, Atsushi; Shibahara, Tomoyuki; Nakamura, Hiroshi; Murata, Koichi; Ushida, Kazunari (Zenodo, 2018)
Fig. 3. Phylogram of E. uekii, type B, other Eimeria spp., and related parasites (Cyclospora spp.) inferred by the neighbor-joining method using partial 18S rRNA gene sequences. Accession numbers and derived hosts are shown in parentheses. Scale bar represents substitutions per nucleotide, and bootstrap values are indicated (> 1000). Cystoisospora spp. are used as an outgroup taxon. Published as part of Matsubayashi, Makoto, Tsuchida, Sayaka, Kobayashi, Atsushi, Shibahara, Tomoyuki, Nakamura, Hiroshi, Murata, Koichi & Ushida, Kazunari, 2018, Molecular identification of two Eimeria species, E. uekii and E. raichoi as type B, in wild Japanese rock ptarmigans, Lagopus muta japonica, pp. 243-250 in International Journal for Parasitology: Parasites and Wildlife 7 (3) on page 247, DOI:10.1016/j.ijppaw.2018.06.005, http://zenodo.org/record/13135846